If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(18 + w) = 56 (18 * 2 + w * 2) = 56 (36 + 2w) = 56 Solving 36 + 2w = 56 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 2w = 56 + -36 Combine like terms: 36 + -36 = 0 0 + 2w = 56 + -36 2w = 56 + -36 Combine like terms: 56 + -36 = 20 2w = 20 Divide each side by '2'. w = 10 Simplifying w = 10
| -4.4s-2=-5-4.2 | | 82-29=18 | | 180=x+50+(180-4x-40) | | 81=a^2 | | r-33-2=11 | | 144=-2-6(6)6(10) | | 8t-2=33+t | | 2k+2=-1313k | | 4K=-9k | | 144=-2-6(6+10) | | 130=3x+2y | | 5x+1+4=11+9x | | 3m+2m+4n+3n= | | 9/4x=1/16 | | 2/3x=140 | | 1=12x-8 | | 5x+8=6x-18 | | 10/9c=-81 | | P-3.2=7.6 | | 7.3y-5.8=51.9 | | 53-2x=5x-17 | | 15+9n=9-n | | 2(7x+2)=-12 | | 2/3z=1/21 | | 50=5ln(3x+7) | | 84=2*35+2*w | | X(8-1)=18 | | -1=2x-8 | | -x/4-5=-8 | | -15+t=20 | | 4/3m=8/15 | | a/3-7=10 |